Characterizing Major Bleeding in Patients With Nonvalvular Atrial Fibrillation: A Pharmacovigilance Study of 27 467 Patients Taking Rivaroxaban. Issue 2 (14th January 2015) - Tamayo, Sally; Frank Peacock, W.; Patel, Manesh; Sicignano, Nicholas; Hopf, Kathleen P.; Fields, Larry E.; Sarich, Troy; Wu, Shujian; Yannicelli, Daniel; Yuan, Zhong
ABSTRACT Background In nonvalvular atrial fibrillation (NVAF), rivaroxaban is used to prevent stroke and systemic embolism. Objective To evaluate major bleeding (MB) in NVAF patients treated with rivaroxaban in a real‐world clinical setting. Methods From January 1, 2013, to March 31, 2014, US Department of Defense electronic health care records were queried to describe MB rates and demographics. Major bleeding was identified using a validated algorithm. Results Of 27 467 patients receiving rivaroxaban, 496 MB events occurred in 478 patients, an incidence of 2.86 per 100 person‐years (95% confidence interval: 2.61‐3.13). The MB patients were older, mean (SD) age of 78.4 (7.7) vs 75.7 (9.7) years, compared with non‐MB patients. Patients with MB had higher rates of hypertension (95.6% vs 75.8%), coronary artery disease (64.2% vs 36.7%), heart failure (48.5% vs 23.7%), and renal disease (38.7% vs 16.7%). Of MB patients, 63.2% were taking 20 mg, 32.2% 15 mg, and 4.6% 10 mg of rivaroxaban. Four percent of MB patients took warfarin within the prior 30 days. Major bleeding was most commonly gastrointestinal (88.5%) or intracranial (7.5%). Although 46.7% of MB patients received a transfusion, none had sufficient evidence of receiving any type of clotting factor. Fourteen died during their MB hospitalization, yielding a fatal bleeding incidence rate of 0.08 per 100 person‐years (95% confidence interval: 0.05‐0.14). Mean age at death was 82.4 years. Conclusions In this large observational study, the MB rate was generally consistent with the registration trial results, and fatal bleeds were rare.